Reflections on language dominance in the absence of vision - Ugarte Rodríguez, Filiberto (2013)
In this article we try to clarify why the domain of language is not halted in the absence of the sense of sight. Our conclusions reveal that, since blindness is not a mental disability, nor does it impede one's capacity to interact with others, it does not therefore interfere with the acquisition, knowledge and use of any given language.